Arsenite removal using a pilot system of ultrasound and ultraviolet followed by microfiltration - Cui, M.; Jang, M.; Ibrahim, S.; Park, B.; Cho, E.; Khim, J. (Elsevier, 2014)
Batch and continuous-flow pilot tests using ultrasound (US), ultraviolet (UV) and a combination of US and UV were conducted to determine the oxidation rates of arsenite [As(III)]. Compared to the single processes of US or UV, the combined US/UV system was more effective for As(III) oxidation with a synergy index of more than 1.5. A high rate constant of As(III) removal was obtained as ferrous [Fe(II)] ions existed. Like the pseudo-Fenton reaction, Fe(II) species can participate in the production of additional ·OH by reacting with H2O2 produced by US, before being oxidized to Fe(III). From the results of batch tests, the optimum molar ratio of Fe(II)/As(III) and pH were found to be 83 and 6-9.5, respectively. Similarly, the continuous-flow pilot tests showed that US/UV system could remove As(III) below the regulation [10 μg L(-1) as total As (Astot)] at 91 of molar ratio [Fe(II)/As(III)] and 3-h HRT. The continuous-stirred-tank-reactor (CSTR) modeling showed that the scavenging effect of anionic species (Cl(-) and CO3(2-)) for ·OH might prevail in the single processes, whereas it is insignificant in the combined process. Without using chemicals, microfiltration (MF) was adopted to treat sludge produced in oxidation step. In terms of an engineering aspect, the operational critical flux (CF) and cycle time were also optimized through the continuous-flow tests of MF system. As an energy-utilizing oxidation technique that does not require a catalyst, the combined energy system employing US/UV followed by MF could be a promising alternative for treating As(III) and Fe(II) simultaneously.